Игрушки: [стихи] / Агния Барто ; художник Олег Горбушин - Барто Агния Львовна (Стихи для малышей, 2012)
Экземпляры: Ф. 4 (20191018) / Инвентарный номер: 43602 / Цена: 51.00 / Сис.шифр: 84(2=411.2)6-44 / Авт.знак: Б 26 / ГРНТИ: 17.82.93 / ББК: 84(2=411.2)6-44